IMPLEMENTATION OF JAKLAPOR AS A DIGITAL PUBLIC COMPLAINT SERVICE ON THE QUALITY OF PUBLIC SERVICES OF DKI JAKARTA - Ralina, Aribah Shafa; Manar, Dzunuwanus Ghulam; Erowati, Dewi - (Journal of Politic and Government Studies, 2024)
DKI Jakarta with over 11 million residents, faces a growing need for efficient public services in the digital age. One key area is handling public complaints. To address this, the DKI Jakarta Provincial Government established JAKI under the President Instruction No.3 of 2003 concerning National Policies and Strategies for E-Government Development and the Presidential Regulation No.95 of 2018 concerning Electronic Based Government Systems. This research aims to discuss the implementation of JAKI as a digital public complaint service on the quality of public services in DKI Jakarta. This research tries to determine if in fact JakLapor, a feature of JAKI, has run optimally as a digital public complaint service. The research was conducted using a qualitative approach. Data collection was obtained through in-depth interviews with 4 staffs of Jakarta Smart City and 5 citizens of DKI Jakarta and through document analysis comprising of papers, books, journals and articles.. Data collection techniques include data analysis and interpretation, data reduction and data presentation. From the research that has been done, there is a result that the implementation of JakLapor has achieved succession in several criteria as seen from the benefits felt by the citizens of DKI Jakarta, the implementing and supervising actors adhering to the Standard Operating Procedures (SOP) regulated in the Decree of the Regional Secretary No.99 of 2022 and functioning in accordance to the relevant regulations, the resources deemed sufficient both financial and human resources, the institution and regime characteristics of JakLapor have also been deemed in accordance to the Governor Regulation No.144 of 2019 and Decree of the Regional Secretary no.99 of 2022. However, there are several setbacks in the running of JakLapor such as the bureaucratic mismatch between the government and the private sectors and the limitation of citizen participation due to the lack of socialization. Furthermore, there are several recommendations to be noted which are to improve communication between government departments and to conduct more thorough socializations